Urgent Versus Delayed Surgical Treatment of Open Distal Radius Fractures: A Multicenter Retrospective Study - Luke Latario, MD; Matthew DeFazio, MD; Matthew Poorman, MD; Alan Shi, MD; Eric Swart, MD; Marci Jones, MD (Journal of Hand Surgery Global Online)
Purpose: Controversy exists on the urgency of operative treatment for low energy open distal radius fractures. Two medical centers shifted practice and no longer take all open distal radius fractures emergently to the operating for debridement. The purpose of this study is to provide preliminary data to evaluate if this is associated with unacceptably high infection rates. Methods: A retrospective chart review was performed for 55 open distal radius fractures in 54 patients at two level one trauma centers. Patients underwent irrigation and closed reduction in the emergency department followed by definitive closed treatment or operative treatment with surgical irrigation, debridement, and fixation, either within 24 hours or after discharge. The main outcome measure was infection, with secondary outcomes of complications or secondary procedures. Results: In this cohort, 4 of 55 patients experienced infections (7.2%.) There were no infections in low energy injuries. Twenty-four patients went to the operating room 2 or more days from presentation or were treated nonoperatively with only 1 postoperative infection (4.2%). All infections were in high energy mechanism injuries with at least one additional risk factor: smoking, polytrauma, or Gustilo Anderson type 2 injury. Conclusions: These data suggest that in patients with low energy injury mechanisms and type 1 injuries, delay in formal operative debridement is not associated with an elevated infection risk in this small case series. Future prospective studies with larger sample sizes are needed to definitively evaluate whether some open distal radius fracture patterns may not require emergent operative debridement. Type of study/level of evidence: Prognostic IV.